MOGUĆNOSTI RAZVITKA GRADA NIŠA KAO SPORTSKO-PENJAČKOG CENTRA - Miloš Puletić; Daniel Stanković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
The main aim of the paper is to present terrains suitable for the development of sports climbing in the vicinity of Nis. It will present the terrains already in the process of development as well as those to be developed in the future. Apart from the natural resources of the vicinity of Nis, the paper will also deal with the existing structures (artificial rocks) in the town itself